Pelatihan Pengembangan Bahan Ajar Berbasis Kearifan Lokal bagi Guru-Guru Bahasa Indonesia SMP Kabupaten Muara Enim - ernalida ernalida (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2022)
The purpose of this service is to train junior high school teachers in the field of Indonesianlanguage studies in Muara Enim Regency in developing teaching materials based on localwisdom. This activity is carried out using training models, lectures, questions and answers,discussions, exercises, and assignments. The implementation of service activities is carriedout on August 22 s.d. 10 September 2022 via offline and online. The target audience isIndonesian Language for junior high school teachers in Muara Enim Regency, totaling 20people. The evaluation design uses tests and observations. The results of the activity showthat teachers' understanding of the development of teaching materials based on local wisdomis still insufficient. This causes the previous learning that has not been carried out using textsbased on Muara Enim local wisdom, even though information close to students can make iteasier for them to explore the material being taught. There are several obstacles in developingfolklore that will be used as teaching materials. Therefore, regular assistance is needed toimprove the work that has been developed by the teachers. The development of the folklorewill be published as a book and is used as teaching material in school.